No evidence for uniparental disomy as a common cause of Sotos syndrome. - Smith, M (1997)
A number of rare diseases (including Sotos syndrome) of unknown aetiology, which occur mainly sporadically and with features of growth disorder and developmental delay, may be caused by imprinted genes and therefore be associated with UPD. Using 112 dinucleotide repeat DNA polymorphisms, we have examined parental inheritance of all autosome pairs, except chromosome 15, in 29 patients with Sotos syndrome. All informative cases showed biparental inheritance and no cases of UPD were found. We conclude that Sotos syndrome is either not caused by an imprinted gene or that UPD is rare or of a segmental form in its aetiology.